Threatened and understudied: the lack of genetic data of endangered Brazilian plant species - Essi, Liliana; Lima, Maria de Fátima Ribeiro Chicatte; Leite, Leandro Gonçalves; Wolf, Mariana Marques (Ciência e Natura, 2020)
A literature review of genetic studies on 3134 endangered or data deficient Brazilian plant species was performed using the Periodical Capes database, using, for each species, a combination of the binomial (without authorship) and the radical genet*. The search was only for articles, without publication year limitation. The search included relevant synonyms, based on information obtained from the National Flora Conservation Center (CNC Flora) website. Phylogenetic studies focusing on taxonomy or studies focusing on gene expression were excluded. A total of 14 463 articles were retrieved with this search strategy, but only 312 fit within the scope of the search. Results show that genetic studies for plants of all threat categories are lacking, with a very low average (0,09%) of genetic studies retrieved per species. The four threatened species with a higher number of studies are species of commercial interest. For 1931 species no article was retrieved. Given the high levels of biodiversity loss in Brazil, it is urgent to invest in the knowledge of the biology of threatened plant species, especially those which are the most neglected in genetic studies.